Social support, quality of life and the women’s perception of practicing a physical training (Research, Society and Development, 2020)
The Quality of life and social support can contribute to healthy aging and motivation to practice physical activities. The objective of this study was to evaluate social support and health-related quality of life (HRQOL) and to understand the experiences of women participating in a physical training program. It was a cross-sectional, exploratory and mixed-design study. Social support was assessed by the Social Support Scale for Adult Physical Activity Practice and HRQOL by the Medical Outcomes Study questionnaire, version 1. The study sample consisted of 17 women, with an average of age of 59.8 years. The HRQOL assessment showed that women had a mean score higher than 80, before and after the beginning of the training program. Likewise, the evaluation of social support showed that most women answered that "never" or "sometimes" received support from family and friends for physical activity. The experiences reported showed improvements in physical, emotional and social aspects. This study showed that the women have little social support for the practice of physical activities and there was no improvement in HRQOL. On the other hand, the women's speech showed improvement in several aspects of everyday life.